2006
DOI: 10.1007/s10545-006-0433-6
|View full text |Cite
|
Sign up to set email alerts
|

The course of life and quality of life of early and continuously treated Dutch patients with phenylketonuria

Abstract: Phenylketonuria (PKU; OMIM 261600) is an autosomal recessive disorder of phenylalanine metabolism caused by a deficiency of the enzyme phenylalanine hydroxylase (PAH; EC 1.14.16.1). Cognitive problems, neuropsychological abnormalities and psychosocial problems have been reported frequently in children and adolescents with PKU, even in those who are treated early and continuously. However, the developmental consequences in adulthood of growing up with PKU are not well known. The aim of this study was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
62
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 21 publications
8
62
2
7
Order By: Relevance
“…[44][45][46][47][48][49] These later effects can be disabling and can result in a lower overall level of educational attainment and socioeconomic status. 50,51 Furthermore, these symptoms make it increasingly difficult for a patient with PAH deficiency to return to metabolic control, since adherence to treatment requires tasks such as planning and organization that rely on intact executive functioning abilities. Therefore, it is recommended that patients be maintained in metabolic control as they move into adulthood.…”
Section: Treatment For Lifementioning
confidence: 99%
“…[44][45][46][47][48][49] These later effects can be disabling and can result in a lower overall level of educational attainment and socioeconomic status. 50,51 Furthermore, these symptoms make it increasingly difficult for a patient with PAH deficiency to return to metabolic control, since adherence to treatment requires tasks such as planning and organization that rely on intact executive functioning abilities. Therefore, it is recommended that patients be maintained in metabolic control as they move into adulthood.…”
Section: Treatment For Lifementioning
confidence: 99%
“…Some previous studies showed differences in respect to final educational attainments (Stemerdink et al 2000, GassiĂł et al 2005), on the other hand a recent Dutch study found no difference between final educational attainments of patients with PKU and the control population (Bosch et al 2007). In our study we could demonstrate that only 4% of our patients had no school certificate, in comparison to 11% of the control population in Leipzig.…”
Section: Respondersmentioning
confidence: 87%
“…Due to PAH deficiency phenylalanine accumulates in body and brain. Untreated PKU patients suffer from severe physical and mental disability (Bosch et al 2007;Scriver et al 1998). Postnatal diagnosis by newborn screening, early treatment with protein restricted diet and substitution of a phenylalanine free amino acid mixture result in a normal cognitive development (Scriver et al 1998;Bremer et al 1997;National Institute of Health Consensus Development 2005).…”
mentioning
confidence: 99%
“…Regarding the evaluation of quality of life (QOL), Enns et al described contrasting results. Out of six studies reviewed, two presented optimal outcomes, i.e., QOL comparable to normal controls [17, 18] and four reported suboptimal results [19–22]. However, more recent studies (published after Enns et al’s review) suggest that the QOL of patients with PKU is often comparable to that of the general population [23–27].…”
Section: Introductionmentioning
confidence: 99%